High-weather-resistance coating and color steel plate prepared from high-weather-resistance coating
By adding graphene and amino modified nanosilica as blended fillers to the aqueous polyurethane coating, the salt spray resistance, hardness and stability of the coating are improved, and the shortcomings of existing aqueous polyurethane coatings in terms of water resistance, corrosion resistance and thermal stability are solved.
Patent Information
- Application Number
- CN202510274831.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-10
AI Technical Summary
The existing water-based polyurethane coatings have shortcomings in water resistance, corrosion resistance and thermal stability, which limits their application in color steel plate finishing engineering.
The aqueous polyurethane is modified by graphene and amino-modified nanosilica as blended fillers. By adjusting the carbon-oxygen ratio of graphene and the particle size of nanosilica, the dispersion and cross-linking ability of the coating are improved.
It significantly improves the salt spray resistance, hardness and stability of the coating, and enhances its anti-corrosion performance and service life on color steel plates.
Smart Images

Figure 2YAF6IQCUHQNO1UUFH42YBTBZWUN8TGTMBG0YR2D 
Figure TSX8WHIL1YP9JUL1DXLPKYQBANGDWAXLTYWDZ00Z
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a highly weather-resistant coating and a color steel plate prepared therefrom. Background Art
[0002] In recent years, the application of color steel plates in the construction industry has become increasingly popular, and the output has been continuously increasing. They are widely used in construction fields such as factories, warehouses, mobile homes, and old house renovations. However, the color steel plates of building structures are affected by sunlight exposure, rain, urban or industrial air pollutants, etc. After a period of time, the surface coating will lose gloss, fade, powder, rust and other problems. Therefore, the problem of color steel plate aging resistance is one of the most prominent problems. For example, the color steel plates used in some projects will have serious surface loss of gloss, fading, rust and other quality problems within 1-2 years of being put into use. Once the above situation occurs, the color steel plates must be maintained or renovated in time to extend their service life. This provides a huge market for the finishing projects of color steel plates, and also puts forward higher requirements for the quality of coating products. How to provide high-performance, environmentally friendly, simple construction, and energy-saving color steel plate finishing coatings has raised new challenges.
[0003] As the finishing layer of color steel plate, the coating integrates multiple functions such as anti-rust, anti-corrosion and decoration. At present, most color steel plate coatings are solvent-based, and the commonly used resins are polyester resin, epoxy resin, polyurethane resin, etc. The biggest disadvantage of this type of coating is that a large amount of organic solvents are used, which wastes resources and pollutes the environment. Therefore, it is the development direction for water-based anti-corrosion coatings to replace traditional solvent-based coatings for the finishing projects of color steel plates. The biggest feature of water-based metal anti-corrosion coatings is that water replaces organic solvents as solvents or dispersion media. It is not only low in price, rich in resources, easy to use, non-toxic, odorless, green and environmentally friendly, but also significantly reduces the use of organic materials and reduces the pollution to the atmosphere caused by the volatilization of organic solvents in coatings. In addition, water is used as a solvent, which is highly safe during storage, construction and transportation, without the risk of explosion or poisoning, and fully meets the requirements of environmental protection.
[0004] Polyurethane is an organic compound obtained by polymerization of polyisocyanate monomers and polyol monomers. Among them, polyol monomers constitute the soft segment in the main chain structure of polyurethane molecules, and polyisocyanate monomers and other small molecule monomers constitute the hard segment in the main chain structure of polyurethane molecules. This unique soft and hard segment molecular structure gives polyurethane excellent properties, including good mechanical properties, wear resistance, flexibility and other material properties. At the same time, it has strong adhesion and good gloss retention, so it has been widely used in many fields such as textile industry, synthetic leather processing, coating, adhesive, ink and fiber. In order to meet the use requirements of different fields, polyurethane with different material properties can be obtained by designing molecular structure, selecting different polyol monomers and polyisocyanate monomers for polymerization, deploying different soft and hard segment content ratios, or performing filler modification.
[0005] As an environmentally friendly material, waterborne polyurethane has received more and more attention from researchers. Waterborne polyurethane is a polyurethane dispersion system with water as the dispersion medium. Unlike traditional solvent-based polyurethane, waterborne polyurethane does not contain organic solvents, is non-toxic and does not pollute the environment. Therefore, it effectively reduces the emission of VOCs during use and meets the needs of green environmental protection. At the same time, in addition to inheriting some of the excellent mechanical properties of solvent-based polyurethane, waterborne polyurethane also has the advantages of low price, easy transportation and storage, good low-temperature film-forming property, relatively convenient use, low-temperature resistance, wear resistance and good adhesion. However, in order to ensure the good dispersion of waterborne polyurethane in water during the preparation process, a large number of hydrophilic groups need to be introduced into the main chain structure of the waterborne polyurethane molecule, thereby increasing the hydrophilicity of the molecular chain, which will greatly reduce the water resistance and corrosion resistance of the waterborne polyurethane. In addition, waterborne polyurethane also has the disadvantages of poor thermal stability, poor solvent resistance, poor surface gloss, and poor coating feel, so its application and promotion are subject to certain restrictions. Therefore, in order to further improve the properties of waterborne polyurethane and expand its scope of application, it is necessary to make necessary modifications to the waterborne polyurethane so that it can meet actual use needs. Summary of the invention
[0006] Based on this, the purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a highly weather-resistant coating and a color steel plate prepared therefrom. The coating has high hardness and good salt spray resistance, and can effectively improve the stability of the color steel plate.
[0007] To achieve the above object, the technical solution adopted by the present invention is: A highly weather-resistant coating comprises the following components in parts by weight: 120-140 parts of aqueous polyurethane dispersion, 7-14 parts of graphene, 3-6 parts of amino-modified nano-silica, 0.2-3 parts of anti-settling agent, 0.2-3 parts of defoaming agent, 0.2-3 parts of wetting dispersant, and 60-100 parts of deionized water; the carbon-oxygen ratio of the graphene is (25-40):1.
[0008] Although waterborne polyurethane has received extensive attention in the field of coating research and application in recent years due to its advantages such as green, environmentally friendly, pollution-free, excellent mechanical properties, wear resistance, bonding properties and toughness, etc., compared with solvent-based polyurethane, due to the presence of hydrophilic groups in the molecular chain structure of waterborne polyurethane, waterborne polyurethane materials currently generally have disadvantages such as poor water resistance and poor chemical resistance, which greatly limits the further development of waterborne polyurethane coatings. Therefore, it is necessary to modify waterborne polyurethane in order to further improve its comprehensive performance, broaden its application scope and extend its service life.
[0009] The present invention adopts graphene and amino-modified nano-silica as blended fillers to modify waterborne polyurethane. The operation process of blending modification is simple and convenient, can be freely selected for matching, the proportion is adjustable, and the economic cost is low. Compared with a single waterborne polyurethane, the water resistance, mechanical properties and other material properties of the blended modified product emulsion are improved to a certain extent. Due to the good hydrophilicity of graphene oxide, the inventors used graphene oxide as a modified filler for waterborne polyurethane in previous work. However, graphene oxide has many defects and poor mechanical properties. It is necessary to add a large amount of other inert fillers at the same time, which is costly and the performance improvement of polyurethane coating is limited. Graphene has unique geometric shape and physical properties: ultra-high specific surface area, excellent mechanical properties, high aspect ratio and excellent barrier properties, as well as advantages such as economical and easy to obtain raw materials. Using graphene as a modified filler can greatly improve the salt spray resistance and hardness of the coating and improve the stability of the coating. The present invention not only gives the graphene surface a certain activity, but also takes into account the mechanical properties of the graphene by selecting graphene with a carbon-oxygen ratio of (25-40):1. When the carbon-oxygen ratio is too low, the graphene surface contains too many oxygen-containing functional groups, the defects increase, and the mechanical properties and barrier properties of the graphene are reduced; when the carbon-oxygen ratio is too high, the oxygen-containing functional groups are too few, the activity is reduced, and the dispersibility in waterborne polyurethane and the bonding performance with the matrix are poor. The oxygen-containing functional groups on the graphene surface are easy to react or form hydrogen bonds with groups such as carbamate, residual isocyanate and hydroxyl in the waterborne polyurethane, further improving the dispersion performance of the graphene in the coating. At the same time, in order to promote the dispersion performance of graphene, the present invention also adds a certain amount of amino-modified nano-silica. The amino-modified nano-silica has good dispersibility in water-based polyurethane, and the presence of active amino groups makes it easy to react with oxygen-containing functional groups on the surface of graphene or residual active groups on polyurethane to form hydrogen bonds, thereby improving the cross-linking ability of silica with graphene and polyurethane with a specific carbon-oxygen ratio, and further improving the density of the coating.
[0010] In addition, during the film-forming and curing process of the coating, due to the volatilization of the solvent, some micropores will inevitably be left in the film layer, and the presence of micropores will affect the corrosion resistance of the film layer. Nano-silicon dioxide can play a filling role to prevent the infiltration of corrosive substances. Furthermore, in the coating, graphene is 9-12 parts and amino-modified nano-silicon dioxide is 3.5-5.5 parts; by adjusting the amount of modifier, it not only improves its dispersion performance, but also promotes the formation of a cross-linked dense structure, thereby improving the corrosion resistance of the coating. When the amount of graphene is small, it is not easy to form a dense cross-linked network and a barrier structure cannot be formed; when the amount of graphene is too much, it faces the problem of difficult dispersion.
[0011] Furthermore, the solid content of the aqueous polyurethane dispersion is 50-70%. The type of aqueous polyurethane is not particularly limited, and it can be prepared by introducing a hydrophilic component in the process of preparing polyurethane. For example, after polyether diol and diisocyanate are reacted for a certain period of time, a hydrophilic chain extender (dimethylolbutyric acid, etc.) and an amine compound are added to continue the reaction to obtain a prepolymer, and then a small molecule diol is added to carry out a chain extension reaction to obtain an aqueous polyurethane dispersion.
[0012] Furthermore, the graphene has a lateral size of 0.5-10 μm. Furthermore, the graphene has a lateral size of 1-3 μm.
[0013] Furthermore, the amino-modified nano-silica is nano-silica modified by an aminosilane coupling agent.
[0014] Furthermore, the specific preparation process of the amino-modified nano-silica is: ultrasonically dispersing the nano-silica in a mixed solution of ethanol and water, then adding an aminosilane coupling agent, and heating for reaction; after the reaction is completed, filtering, washing, and drying to obtain the amino-modified nano-silica.
[0015] Furthermore, the volume average particle size (D50) of the nano-silica is 20-100nm. Specifically, it can be 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, etc. In particular, the volume average particle size of nano-silica is 40-70nm. By adjusting the particle size of nano-silica, its enhancement and dispersion properties can be taken into account. If the particle size is too small, as the particle size decreases, the specific surface area of the nanoparticles increases, the number of surface atoms increases, and the number of atoms with unsaturated surface coordination also increases sharply, resulting in the nanoparticles having a very high surface energy. This high energy state makes the nanoparticles very unstable and prone to agglomeration to reach a stable state, and the nano effect of the nanoparticles cannot be fully exerted. If the particle size is too large, it cannot be combined with graphene and dispersed, and it cannot play the role of blocking micropores.
[0016] Furthermore, the aminosilane coupling agent is one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-β (aminoethyl) -γ-aminopropyltrimethoxysilane, N-β (aminoethyl) -γ-aminopropylmethyldimethoxysilane, and N-β (aminoethyl) -γ-aminopropyltriethoxysilane.
[0017] Furthermore, the heating reaction temperature is 50-60°C, and the reaction time is 1-2h. The mass ratio of the aminosilane coupling agent to the nano-silicon dioxide is (0.3-0.6):1.
[0018] Furthermore, the types of anti-settling agent, defoaming agent and wetting and dispersing agent are not particularly limited, and any common types in the art may be used. Specifically, the anti-settling agent is a mixture of one or more of BYK420, BYK425 and BYK430; the defoaming agent is an organosilicon defoaming agent or a mineral oil defoaming agent; and the wetting and dispersing agent is a mixture of one or more of polyacrylic acid sodium salt, polyacrylic acid ammonium salt and polyphosphate.
[0019] Furthermore, the preparation method of the highly weather-resistant coating comprises the following steps: S1. Weigh each component by weight; S2. After graphene, amino-modified nano-silica and deionized water are evenly mixed, an aqueous polyurethane dispersion is added, and the mixture is dispersed by stirring. Then, an anti-settling agent, a defoaming agent and a wetting dispersant are added, and the mixture is evenly mixed again to obtain a highly weather-resistant coating.
[0020] On the other hand, the present invention provides a color steel plate, which is prepared by coating a highly weather-resistant coating on the surface of the cleaned color steel plate.
[0021] Beneficial effects: The present invention uses graphene and amino-modified nano-silica as blended fillers to modify waterborne polyurethane. By selecting graphene with a carbon-oxygen ratio of (25-40):1, the graphene surface is given a certain activity, while the mechanical properties of the graphene are taken into account, and the dispersion performance of the graphene in the coating is further improved. The amino-modified nano-silica has good dispersibility in waterborne polyurethane, and the presence of active amino groups is also easy to react with oxygen-containing functional groups on the graphene surface or active groups remaining on the polyurethane and form hydrogen bonds, thereby improving its cross-linking ability with graphene and polyurethane with a specific carbon-oxygen ratio, further promoting the formation of a cross-linked dense structure, and improving the anti-corrosion performance of the coating. DETAILED DESCRIPTION
[0022] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. In the embodiments, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0023] Example 1 A highly weather-resistant coating comprises the following components in parts by weight: 120 parts of aqueous polyurethane dispersion, 9 parts of graphene, 3 parts of amino-modified nano-silicon dioxide, 1 part of anti-settling agent, 2 parts of defoaming agent, 0.5 parts of wetting dispersant, and 60 parts of deionized water; the carbon-oxygen ratio of the graphene is 25:1; the solid content of the aqueous polyurethane dispersion is 60%; the average lateral size of the graphene is 2 μm; the specific preparation process of the amino-modified nano-silicon dioxide is: ultrasonically dispersing the nano-silicon dioxide in a mixed solution of ethanol and water, and then adding Adding aminosilane coupling agent, heating reaction; filtering, washing and drying after the reaction is completed to obtain amino-modified nano-silica; the volume average particle size of the nano-silica is 40nm; the aminosilane coupling agent is 3-aminopropyltriethoxysilane; the heating reaction temperature is 50°C, and the reaction time is 2h; the mass ratio of the aminosilane coupling agent to the nano-silica is 0.3:1; the anti-settling agent is BYK430; the defoaming agent is polydimethylsiloxane; the wetting and dispersing agent is polyacrylate ammonium salt.
[0024] Example 2 A highly weather-resistant coating comprises the following components in parts by weight: 140 parts of aqueous polyurethane dispersion, 12 parts of graphene, 6 parts of amino-modified nano-silicon dioxide, 3 parts of anti-settling agent, 3 parts of defoaming agent, 3 parts of wetting dispersant, and 90 parts of deionized water; the carbon-oxygen ratio of the graphene is 40:1; the solid content of the aqueous polyurethane dispersion is 60%; the average lateral size of the graphene is 2 μm; the specific preparation process of the amino-modified nano-silicon dioxide is: ultrasonically dispersing the nano-silicon dioxide in a mixed solution of ethanol and water, and then adding Adding aminosilane coupling agent, heating reaction; filtering, washing and drying after the reaction is completed to obtain amino-modified nano-silica; the volume average particle size of the nano-silica is 70nm; the aminosilane coupling agent is 3-aminopropyltrimethoxysilane; the heating reaction temperature is 60°C, and the reaction time is 1h; the mass ratio of the aminosilane coupling agent to the nano-silica is 0.6:1; the anti-settling agent is BYK425; the defoaming agent is polydimethylsiloxane; the wetting and dispersing agent is sodium polyacrylate.
[0025] Example 3 A highly weather-resistant coating comprises the following components in parts by weight: 120 parts of aqueous polyurethane dispersion, 12 parts of graphene, 3 parts of amino-modified nano-silicon dioxide, 3 parts of anti-settling agent, 0.8 parts of defoaming agent, 2.6 parts of wetting dispersant, and 85 parts of deionized water; the carbon-oxygen ratio of the graphene is 25:1; the solid content of the aqueous polyurethane dispersion is 60%; the average lateral size of the graphene is 2 μm; the specific preparation process of the amino-modified nano-silicon dioxide is: ultrasonically dispersing the nano-silicon dioxide in a mixed solution of ethanol and water, and then The aminosilane coupling agent is added and heated for reaction; after the reaction is completed, the mixture is filtered, washed and dried to obtain amino-modified nano-silica; the volume average particle size of the nano-silica is 40 nm; the aminosilane coupling agent is 3-aminopropyltriethoxysilane; the heating reaction temperature is 55° C., and the reaction time is 1.3 h; the mass ratio of the aminosilane coupling agent to the nano-silica is 0.3:1; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.
[0026] Example 4 A highly weather-resistant coating comprises the following components in parts by weight: 125 parts of aqueous polyurethane dispersion, 10 parts of graphene, 3.5 parts of amino-modified nano-silicon dioxide, 1.2 parts of anti-settling agent, 1.1 parts of defoaming agent, 1.4 parts of wetting dispersant, and 70 parts of deionized water; the carbon-oxygen ratio of the graphene is 30:1; the solid content of the aqueous polyurethane dispersion is 60%; the average lateral size of the graphene is 2 μm; the specific preparation process of the amino-modified nano-silicon dioxide is: ultrasonically dispersing the nano-silicon dioxide in a mixed solution of ethanol and water, Then, an aminosilane coupling agent is added and heated to react; after the reaction is completed, the mixture is filtered, washed and dried to obtain amino-modified nano-silica; the volume average particle size of the nano-silica is 50 nm; the aminosilane coupling agent is 3-aminopropyltriethoxysilane; the heating reaction temperature is 52° C., and the reaction time is 1.8 h; the mass ratio of the aminosilane coupling agent to the nano-silica is 0.4:1; the anti-settling agent is BYK430; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.
[0027] Example 5 A highly weather-resistant coating comprises the following components in parts by weight: 130 parts of aqueous polyurethane dispersion, 11 parts of graphene, 5 parts of amino-modified nano-silicon dioxide, 2.5 parts of anti-settling agent, 2.1 parts of defoaming agent, 2 parts of wetting dispersant, and 85 parts of deionized water; the carbon-oxygen ratio of the graphene is 35:1; the solid content of the aqueous polyurethane dispersion is 60%; the average lateral size of the graphene is 2 μm; the specific preparation process of the amino-modified nano-silicon dioxide is: ultrasonically dispersing the nano-silicon dioxide in a mixed solution of ethanol and water, and then The aminosilane coupling agent is added and heated for reaction; after the reaction is completed, the mixture is filtered, washed and dried to obtain amino-modified nano-silica; the volume average particle size of the nano-silica is 60 nm; the aminosilane coupling agent is 3-aminopropyltrimethoxysilane; the heating reaction temperature is 58° C., and the reaction time is 1.3 h; the mass ratio of the aminosilane coupling agent to the nano-silica is 0.5:1; the anti-settling agent is BYK425; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is ammonium polyacrylate.
[0028] Example 6 A highly weather-resistant coating comprises the following components in parts by weight: 130 parts of aqueous polyurethane dispersion, 7 parts of graphene, 4 parts of amino-modified nano-silicon dioxide, 1 part of anti-settling agent, 1.5 parts of defoaming agent, 1.2 parts of wetting dispersant, and 80 parts of deionized water; the carbon-oxygen ratio of the graphene is 30:1; the solid content of the aqueous polyurethane dispersion is 60%; the average lateral size of the graphene is 2 μm; the specific preparation process of the amino-modified nano-silicon dioxide is: ultrasonically dispersing the nano-silicon dioxide in a mixed solution of ethanol and water, and then adding Adding aminosilane coupling agent, heating reaction; filtering, washing and drying after the reaction is completed to obtain amino-modified nano-silica; the volume average particle size of the nano-silica is 50nm; the aminosilane coupling agent is 3-aminopropyltriethoxysilane; the heating reaction temperature is 54°C, and the reaction time is 1.5h; the mass ratio of the aminosilane coupling agent to the nano-silica is 0.5:1; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; the wetting and dispersing agent is sodium polyacrylate.
[0029] Example 7 A highly weather-resistant coating comprises the following components in parts by weight: 130 parts of aqueous polyurethane dispersion, 14 parts of graphene, 4 parts of amino-modified nano-silicon dioxide, 1 part of anti-settling agent, 1.5 parts of defoaming agent, 1.2 parts of wetting dispersant, and 80 parts of deionized water; the carbon-oxygen ratio of the graphene is 30:1; the solid content of the aqueous polyurethane dispersion is 60%; the average lateral size of the graphene is 2 μm; the specific preparation process of the amino-modified nano-silicon dioxide is: ultrasonically dispersing the nano-silicon dioxide in a mixed solution of ethanol and water, and then The aminosilane coupling agent is added and heated for reaction; after the reaction is completed, the mixture is filtered, washed and dried to obtain amino-modified nano-silica; the volume average particle size of the nano-silica is 50 nm; the aminosilane coupling agent is 3-aminopropyltriethoxysilane; the heating reaction temperature is 54° C. and the reaction time is 1.5 h; the mass ratio of the aminosilane coupling agent to the nano-silica is 0.5:1; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.
[0030] Example 8 A highly weather-resistant coating comprises the following components in parts by weight: 130 parts of aqueous polyurethane dispersion, 10 parts of graphene, 4 parts of amino-modified nano-silicon dioxide, 1 part of anti-settling agent, 1.5 parts of defoaming agent, 1.2 parts of wetting dispersant, and 80 parts of deionized water; the carbon-oxygen ratio of the graphene is 30:1; the solid content of the aqueous polyurethane dispersion is 60%; the average lateral size of the graphene is 2 μm; the specific preparation process of the amino-modified nano-silicon dioxide is: ultrasonically dispersing the nano-silicon dioxide in a mixed solution of ethanol and water, and then The aminosilane coupling agent is added and heated for reaction; after the reaction is completed, the mixture is filtered, washed and dried to obtain amino-modified nano-silica; the volume average particle size of the nano-silica is 20 nm; the aminosilane coupling agent is 3-aminopropyltriethoxysilane; the heating reaction temperature is 54° C. and the reaction time is 1.5 h; the mass ratio of the aminosilane coupling agent to the nano-silica is 0.5:1; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.
[0031] Example 9 A highly weather-resistant coating comprises the following components in parts by weight: 130 parts of aqueous polyurethane dispersion, 10 parts of graphene, 4 parts of amino-modified nano-silicon dioxide, 1 part of anti-settling agent, 1.5 parts of defoaming agent, 1.2 parts of wetting dispersant, and 80 parts of deionized water; the carbon-oxygen ratio of the graphene is 30:1; the solid content of the aqueous polyurethane dispersion is 60%; the average lateral size of the graphene is 2 μm; the specific preparation process of the amino-modified nano-silicon dioxide is: ultrasonically dispersing the nano-silicon dioxide in a mixed solution of ethanol and water, and then adding Adding aminosilane coupling agent, heating reaction; filtering, washing and drying after the reaction is completed to obtain amino-modified nano-silica; the volume average particle size of the nano-silica is 100nm; the aminosilane coupling agent is 3-aminopropyltriethoxysilane; the heating reaction temperature is 54°C, and the reaction time is 1.5h; the mass ratio of the aminosilane coupling agent to the nano-silica is 0.5:1; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; the wetting and dispersing agent is sodium polyacrylate.
[0032] Example 10 A highly weather-resistant coating comprises the following components in parts by weight: 130 parts of aqueous polyurethane dispersion, 10 parts of graphene, 4 parts of amino-modified nano-silicon dioxide, 1 part of anti-settling agent, 1.5 parts of defoaming agent, 1.2 parts of wetting dispersant, and 80 parts of deionized water; the carbon-oxygen ratio of the graphene is 30:1; the solid content of the aqueous polyurethane dispersion is 60%; the average lateral size of the graphene is 2 μm; the specific preparation process of the amino-modified nano-silicon dioxide is: ultrasonically dispersing the nano-silicon dioxide in a mixed solution of ethanol and water, and then The aminosilane coupling agent is added and heated for reaction; after the reaction is completed, the mixture is filtered, washed and dried to obtain amino-modified nano-silica; the volume average particle size of the nano-silica is 50 nm; the aminosilane coupling agent is 3-aminopropyltriethoxysilane; the heating reaction temperature is 54° C. and the reaction time is 1.5 h; the mass ratio of the aminosilane coupling agent to the nano-silica is 0.5:1; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.
[0033] Comparative Example 1 A highly weather-resistant coating comprises the following components in parts by weight: 130 parts of aqueous polyurethane dispersion, 0 parts of graphene, 14 parts of amino-modified nano-silicon dioxide, 1 part of anti-settling agent, 1.5 parts of defoaming agent, 1.2 parts of wetting dispersant, and 80 parts of deionized water; the aqueous polyurethane dispersion has a solid content of 60%; the specific preparation process of the amino-modified nano-silicon dioxide is: ultrasonically dispersing nano-silicon dioxide in a mixed solution of ethanol and water, then adding an aminosilane coupling agent, and heating for reaction; After the reaction is completed, the mixture is filtered, washed and dried to obtain amino-modified nano-silica; the volume average particle size of the nano-silica is 50 nm; the aminosilane coupling agent is 3-aminopropyltriethoxysilane; the heating reaction temperature is 54° C., and the reaction time is 1.5 h; the mass ratio of the aminosilane coupling agent to the nano-silica is 0.5:1; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.
[0034] Comparative Example 2 A highly weather-resistant coating comprises the following components in parts by weight: 130 parts of an aqueous polyurethane dispersion, 14 parts of graphene, 0 parts of amino-modified nano-silica, 1 part of an anti-settling agent, 1.5 parts of a defoaming agent, 1.2 parts of a wetting and dispersing agent, and 80 parts of deionized water; the carbon-oxygen ratio of the graphene is 30:1; the solid content of the aqueous polyurethane dispersion is 60%; the average lateral size of the graphene is 2 μm; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.
[0035] Comparative Example 3 A highly weather-resistant coating comprises the following components in parts by weight: 130 parts of aqueous polyurethane dispersion, 10 parts of graphene, 4 parts of amino-modified nano-silicon dioxide, 1 part of anti-settling agent, 1.5 parts of defoaming agent, 1.2 parts of wetting dispersant, and 80 parts of deionized water; the carbon-oxygen ratio of the graphene is 15:1; the solid content of the aqueous polyurethane dispersion is 60%; the average lateral size of the graphene is 2 μm; the specific preparation process of the amino-modified nano-silicon dioxide is: ultrasonically dispersing the nano-silicon dioxide in a mixed solution of ethanol and water, and then The aminosilane coupling agent is added and heated for reaction; after the reaction is completed, the mixture is filtered, washed and dried to obtain amino-modified nano-silica; the volume average particle size of the nano-silica is 50 nm; the aminosilane coupling agent is 3-aminopropyltriethoxysilane; the heating reaction temperature is 54° C. and the reaction time is 1.5 h; the mass ratio of the aminosilane coupling agent to the nano-silica is 0.5:1; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.
[0036] Comparative Example 4 A highly weather-resistant coating comprises the following components in parts by weight: 130 parts of aqueous polyurethane dispersion, 10 parts of graphene, 4 parts of amino-modified nano-silicon dioxide, 1 part of anti-settling agent, 1.5 parts of defoaming agent, 1.2 parts of wetting dispersant, and 80 parts of deionized water; the carbon-oxygen ratio of the graphene is 50:1; the solid content of the aqueous polyurethane dispersion is 60%; the average lateral size of the graphene is 2 μm; the specific preparation process of the amino-modified nano-silicon dioxide is: ultrasonically dispersing the nano-silicon dioxide in a mixed solution of ethanol and water, and then The aminosilane coupling agent is added and heated for reaction; after the reaction is completed, the mixture is filtered, washed and dried to obtain amino-modified nano-silica; the volume average particle size of the nano-silica is 50 nm; the aminosilane coupling agent is 3-aminopropyltriethoxysilane; the heating reaction temperature is 54° C. and the reaction time is 1.5 h; the mass ratio of the aminosilane coupling agent to the nano-silica is 0.5:1; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.
[0037] Comparative Example 5 A highly weather-resistant coating comprises the following components in parts by weight: 130 parts of aqueous polyurethane dispersion, 10 parts of graphene, 9 parts of amino-modified nano-silicon dioxide, 1 part of anti-settling agent, 1.5 parts of defoaming agent, 1.2 parts of wetting dispersant, and 80 parts of deionized water; the carbon-oxygen ratio of the graphene is 30:1; the solid content of the aqueous polyurethane dispersion is 60%; the average lateral size of the graphene is 2 μm; the specific preparation process of the amino-modified nano-silicon dioxide is: ultrasonically dispersing the nano-silicon dioxide in a mixed solution of ethanol and water, and then The aminosilane coupling agent is added and heated for reaction; after the reaction is completed, the mixture is filtered, washed and dried to obtain amino-modified nano-silica; the volume average particle size of the nano-silica is 50 nm; the aminosilane coupling agent is 3-aminopropyltriethoxysilane; the heating reaction temperature is 54° C. and the reaction time is 1.5 h; the mass ratio of the aminosilane coupling agent to the nano-silica is 0.5:1; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.
[0038] The specific preparation process of the high weather-resistant coating of the above embodiment and comparative example includes the following steps: S1. Weigh each component by weight; S2. After graphene, amino-modified nano-silica and deionized water are evenly mixed, an aqueous polyurethane dispersion is added, and the mixture is dispersed by stirring. Then, an anti-settling agent, a defoaming agent and a wetting dispersant are added, and the mixture is evenly mixed again to obtain a highly weather-resistant coating.
[0039] Performance test: The high weather-resistant coatings prepared in Examples 1-10 and Comparative Examples 1-5 were subjected to hardness test (GB / T6739-2006), paint film adhesion test (GB / T 5210-2006), and salt spray resistance test (GB / T 1771-2007); the results are shown in Table 1.
[0040] Table 1 Performance of high weather-resistant coatings prepared in Examples 1-10 and Comparative Examples 1-5 Table 1 As can be seen from Table 1, the present invention uses graphene and amino-modified nano-silica as blended fillers to modify waterborne polyurethane. Compared with a single waterborne polyurethane, the corrosion resistance, adhesion and other material properties of the blended modified product are improved to a certain extent. From Example 10 and Comparative Examples 1-2, it can be seen that the present invention not only gives the graphene surface a certain activity by selecting a graphene with a carbon-oxygen ratio of (25-40): 1, but also takes into account the mechanical properties of the graphene. The amino-modified nano-silica has good dispersibility in waterborne polyurethane, and the presence of active amino groups is also easy to react with oxygen-containing functional groups on the graphene surface or active groups remaining on the polyurethane and form hydrogen bonds, thereby improving its cross-linking ability with graphene and polyurethane with a specific carbon-oxygen ratio, and further improving the compactness of the coating to improve its salt spray resistance. Among them, lamellar graphene can form a connection structure with amino-modified nano-silicon dioxide due to the presence of certain oxygen-containing active groups; during the co-mixing and stirring process, lamellar graphene with a specific carbon-oxygen ratio and amino-modified granular nano-silicon dioxide assist each other and promote each other's dispersion; while the simple addition of graphene will cause the graphene to merge and stack in the solvent, and its barrier effect cannot be fully exerted; simple silicon dioxide is also prone to agglomeration due to the lack of barrier of lamellar structure. Comparative Examples 1-2 show that graphene with a single lamellar morphology or granular silicon dioxide has the technical problem of uneven dispersion, resulting in a decrease in coating performance.
[0041] Comparative Examples 3-4 show that when the carbon-oxygen ratio is too low, there are too many oxygen-containing functional groups on the graphene surface, and the defects increase, resulting in reduced mechanical properties and barrier properties of graphene, and excessive cross-linking with polyurethane and amino-modified nano-silica may occur, making it difficult to disperse evenly; when the carbon-oxygen ratio is too high, there are too few oxygen-containing functional groups, the activity is reduced, and the dispersibility in water-based polyurethane is poor, and it is impossible to form a cross-linked structure with amino-modified nano-silica. Comparative Example 5 shows that the dispersibility of amino-modified nano-silica in water-based polyurethane is good, and the presence of active amino groups is also easy to react with oxygen-containing functional groups on the graphene surface or active groups remaining on polyurethane and form hydrogen bonds, which improves its cross-linking ability with graphene and polyurethane of a specific carbon-oxygen ratio, and further improves the compactness of the coating; however, when it is used in too much amount, it not only fails to promote the dispersion of graphene, but also faces the problem of difficulty in dispersion.
[0042] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A highly weather-resistant coating, characterized in that: Contains the following components in parts by weight: 120-140 parts of aqueous polyurethane dispersion, 7-14 parts of graphene, 3-6 parts of amino-modified nano-silica, 0.2-3 parts of anti-settling agent, 0.2-3 parts of defoaming agent, 0.2-3 parts of wetting dispersant, and 60-100 parts of deionized water; the carbon-oxygen ratio of the graphene is (25-40):
1.
2. A highly weather-resistant coating as claimed in claim 1, characterized in that: The solid content of the aqueous polyurethane dispersion is 50-70%.
3. A highly weather-resistant coating as claimed in claim 1, characterized in that: The graphene has a lateral size of 0.5-10 μm.
4. A highly weather-resistant coating as claimed in claim 1, characterized in that: The amino-modified nano-silica is nano-silica modified by an aminosilane coupling agent.
5. A highly weather-resistant coating as claimed in claim 1, characterized in that: The specific preparation process of the amino-modified nano-silica is as follows: dispersing the nano-silica in a mixed solution of ethanol and water by ultrasonication, then adding an aminosilane coupling agent, and heating for reaction; after the reaction is completed, filtering, washing, and drying to obtain the amino-modified nano-silica.
6. A highly weather-resistant coating as claimed in claim 5, characterized in that: The volume average particle size of the nano silicon dioxide is 20-100 nm.
7. A highly weather-resistant coating as claimed in claim 5, characterized in that: The aminosilane coupling agent is one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-β (aminoethyl) -γ-aminopropyltrimethoxysilane, N-β (aminoethyl) -γ-aminopropylmethyldimethoxysilane, and N-β (aminoethyl) -γ-aminopropyltriethoxysilane.
8. A highly weather-resistant coating as claimed in claim 5, characterized in that: The temperature of the heating reaction is 50-60° C., and the reaction time is 1-2 hours; the mass ratio of the aminosilane coupling agent to the nano-silicon dioxide is (0.3-0.6):
1.
9. A highly weather-resistant coating as claimed in claim 1, characterized in that: The preparation method of the highly weather-resistant coating comprises the following steps: S1. Weigh each component by weight; S2. After graphene, amino-modified nano-silica and deionized water are evenly mixed, an aqueous polyurethane dispersion is added, and the mixture is dispersed by stirring. Then, an anti-settling agent, a defoaming agent and a wetting dispersant are added, and the mixture is evenly mixed again to obtain a highly weather-resistant coating.
10. A color steel plate, characterized in that: The highly weather-resistant coating according to any one of claims 1 to 9 is coated on the surface of a cleaned color steel plate to obtain the coating.
Citation Information
Patent Citations
Graphene-silica hybrid material and method for preparing polyurethane based nanocomposite
CN106221179A
Preparation method of modified water-based polyurethane coating
CN107828328A
Modified graphene oxide composite waterborne polyurethane environment-friendly anticorrosive coating
CN111154392A
Cited By
High-performance coating and color steel plate prepared from high-performance coating
CN120554941A
Coating for galvanized sheet and preparation method thereof
CN121801441A